Penyisipan Pesan Pada File Dokumen Berekstensi Xls/Xlsx Menggunakan Metode Chinese Remainder - Cici Ulandari (STMIK Budi Darma, 2022)
Information which is the result of processing from data has a different value for each person. Often information becomes very valuable and not everyone is allowed to know it, but there are always parties who try to find out information in ways that are not supposed to even intend to destroy it. There are several methods in steganography, one of which is a method to hide secret messages (text or images) in other files that contain text, images, and even audio without showing any real or visible changes in the quality and structure of the original file. . These methods include invisible ink, microdots, word management, digital signatures, hidden paths and wide spectrum communications. Chineses Reminder Theorem (CRT) is a concept based on a congruent relationship. However, unlike congruence in general, this concept is based on a simultaneous congruence relationship. Simultaneous congruence refers to several congruent relations that have a relationship with each other, and this relationship is related to the value of the same variable but with different modulo. This theory is an ancient theory that is often used in cryptography applications.